QUALITY OF LIFE OF USERS OF LONG-TERM HEALTH CARE - Zlatanović, Milena; Osmanspahić, Adnan; Despotović, Mile; Hadživuković, Natalija; Pavlović, Jelena; Matović, Sandra; Živanović, Srđan; Zlatanović, Milena; Despotović, Milena; Kucurski, Ljubiša (PONS - medicinski časopis, 2024)
Introduction. Long-term care represents a series of health and social care services that are provided at home or in an institutional environment to people with reduced functional capacity (reduced physical and/or cognitive abilities) who need support in performing daily activities, and who depend on the help of others for a long time period. The goal of the research was to examine the quality of life of users with long-term health care, with a special focus on comparing the quality of life between people placed institutionally and outside of the institution.        Methods. The research was designed according to the principle of a cross-sectional study. In the research, a general questionnaire and a scale for assessing the quality of life Short Form 36 Health Survey (SF-36) were used. Among the statistical tests, the χ2 square test was used. The usual value of p
Keywords: Long-term health care, quality of life, institutional users, non-institutional users.